Трудо-правовий статус авіаційного персоналу в системі Міністерства внутрішніх справ України та його особливості - Бершадська, Ю. В.; Bershadska, Yu. V.; ORCID: http://orcid.org/0000-0001-7699-1208 (Право і безпека. – 2023. – № 1 (88). – С. 13-24, 2023)
Розглянуто поняття «трудо-правовий статус авіаційного персоналу в системі Міністерства внутрішніх справ України», визначено й охарактеризовано його особливості. Досліджено теоретичні підходи до визначення понять «статус», «соціальний статус», «правовий статус», «трудова правосуб’єктність», елементів трудо-правого статусу працівника. Проаналізовано вимоги, що висуваються до суб’єктів авіаційного персоналу, особливостей професійної підготовки та виконання трудових функцій авіаційного персоналу. Обґрунтовано, що авіаційний персонал системи Міністерства внутрішніх справ виконує серед іншого правоохоронну функцію, наділений особливим трудо-правовим статусом, який регламентується не тільки загальним законодавством, а й спеціальним.

The relevance and necessity of analyzing and thoroughly researching the issue of legal regulation of aviation personnel’s labor in the system of the Ministry of Internal Affairs of Ukraine is due to the specific focus of aviation personnel’s labor activity, unlike other mass professions and specialties, the use of sources of the increased danger, the strenuous nature of work, and variou s external conditions under which the labor function is realized,as well as the availability of proper health conditions defined by standards and requirements, mandatory certification and admission of aviation personnel to activities in the aviation industry,the mandatory certification and admission of aviation personnel to activities in the aviation industry, and the performance by aviation personnel, along with their professional duties, of a law enforcement function aimed at ensuring and maintaining order in the State and society, and increasing the country’s defense capability.Therefore, the solution of problems arising within the framework of labor relations in the field of aviation is one of the important components of the analysis of the labor and legal status of aviation personnel in the aviation component of the Ministry of Internal Affairs system. Based on the analysis of scientific views of scholars, it has been examined theoretical approaches to the definition of the concepts of “status”, “social status”, “legal status”, “labor legal personality”, and elements of the employee’s labor and legal status; based on the analysis of regulations, the author has examined the requirements for aviation personnel.It has been de-termined the peculiarities of the labor and legal status of aviation personnel in thesystem of the Ministry of Internal Affairs of Ukraine: aviation orientation of the labor function; compliance with the qualification requirements on a professional basis, which involves mastering knowledge in the aviation industry, practical preparedness and training of flight personnel, special requirements regarding age, health status of a person, and proper knowledge of a foreign language; mandatory certification and admission of aviation personnel to aviation activities in accordance with the aviation rules of Ukraine, availability of a duly issued certificate; regulation of the labor status of aviation personnel by both general and specialrules; performance of law enforcement functions by aviation personnel in the system of the Ministry of Internal Af fairs of Ukraine aimed at realization of the interests of the state extremely important for the protection of law and order and security in the state and society; special regulation of working hours, rest periods, responsibilities, and guarantees that contribute to the stability of labor relations. Considering the established features, it has beendefined the labor and legal status of aviation personnel in the system of the Ministry of Internal Affairs of Ukraine.

Рассмотрено понятие «трудо-правовой статус авиационного персонала в системе Министерства внутренних дел Украины», определены и охарактеризованы его особенности. Исследованы теоретические подходы к определению понятий «статус», «социальный статус», «правовой статус», «трудовая правосубъектность», элементов трудо-правого статуса работника. Проанализированы требования к субъектам авиационного персонала, особенностям профессиональной подготовки и выполнения трудовых функций авиационного персонала. Обосновано, что авиационный персонал системы Министерства внутренних дел выполняет среди прочего правоохранительную функцию, наделен особым трудо-правовым статусом, который регламентируется не только общим законодательством, но и специальным.
Labor and legal status of aviation personnel in the system of the Ministry of Internal Affairs of Ukraine and its peculiarities
Трудо-правовой статус авиационного персонала в системе Министерства внутренних дел Украины и его особенности
Бершадська, Ю. В. Трудо-правовий статус авіаційного персоналу в системі Міністерства внутрішніх справ України та його особливості / Юлія Володимирівна Бершадська // Право і безпека. – 2023. – № 1 (88). – С. 13-24. - DOI: https://doi.org/10.32631/pb.2023.1.01.
Бершадська Ю. В. Трудо-правовий статус авіаційного пер-соналу в системі Міністерства внутрішніх справ України та його особливості. Право і безпека. 2023. No 1 (88). С. 13–24. DOI: https:// doi.org/10.32631/pb.2023.1.01.
Bershadska, Yu. V. (2023). Laborand legal status of aviation personnel in the system of the Ministry of Internal Affairs of Ukraine and its peculiarities. Law and Safety, 1(88), 13–24. https:// doi.org/10.32631/pb.2023.1.01.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; авіаційний персонал; aviation personnel; авиационный персонал; правовий статус; legal status; правовой статус; авіаційний персонал в системі Міністерства внутрішніх справ; трудо-правовий статус; labor legal status; трудо-правовой статус; трудова функція; labor function; трудовая функция; трудова правосуб’єктність; labor legal personality; трудовая правосубъектность